FOUR NEW RECORDS OF PROSOBRANCH GASTROPODS FROM MANDAPAM - Unnithan, Asokakumaran (Indian Journal of Fisheries, 2011)
Four prosobranch gastropods Epitonium scalaris (Linnaeus), Capulus Sp., Bursct crumena (Lamarck) and Turris indica Reding, recorded for the first time, from Mandapam area are described